2008
DOI: 10.1103/physrevlett.100.186402
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure, Phonons, and Dielectric Anomaly in Ferromagnetic Insulating Double PervoskiteLa2NiMnO6

Abstract: Using first-principles density functional calculations, we study the electronic and magnetic properties of the ferromagnetic insulating double perovskite compound La2NiMnO6, which has been reported to exhibit an interesting magnetic field sensitive dielectric anomaly as a function of temperature. Our study reveals the existence of very soft infrared active phonons that couple strongly with spins at the Ni and Mn sites through modification of the superexchange interaction. We suggest that these modes are the or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
115
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(132 citation statements)
references
References 16 publications
15
115
2
Order By: Relevance
“…[15][16][17] In La 2 NiMnO 6 , the Ni-Mn ferromagnetic exchange interaction J Ni-Mn (H = −2J S i · S j ) depends on Ni-O-Mn angle (θ ), as cos 2 (θ ). 18 Booth et. al. have investigated the structural as well as magnetic properties of A 2 NiMnO 6 , they found that the ferromagnetic Curie temperature of these double perovskite series has better connection with radius of A 3+ ions than with average Ni-O-Mn angle.…”
mentioning
confidence: 99%
“…[15][16][17] In La 2 NiMnO 6 , the Ni-Mn ferromagnetic exchange interaction J Ni-Mn (H = −2J S i · S j ) depends on Ni-O-Mn angle (θ ), as cos 2 (θ ). 18 Booth et. al. have investigated the structural as well as magnetic properties of A 2 NiMnO 6 , they found that the ferromagnetic Curie temperature of these double perovskite series has better connection with radius of A 3+ ions than with average Ni-O-Mn angle.…”
mentioning
confidence: 99%
“…Electronic correlation effects are considered by using GGA þ U (rotationally invariant approach) with U eff ¼ 3 eV for Mn, CO, and Ni, which are typical values used in the literature. [11][12][13] Projected augmented wave (PAW) potentials 22 were used, and the kinetic energy cutoff for expansion of wave functions was 400 eV. Reciprocal space integrations were carried out with a k-space mesh of 7 Â 7 Â 5.…”
mentioning
confidence: 99%
“…1,2 Double perovskite La 2 NiMnO 6 (LNMO) and La 2 CoMnO 6 (LCMO) are attractive due to their impressive properties and potential on industrial applications. [3][4][5][6][7][8][9][10][11][12][13] LNMO is a ferromagnetic semiconductor with high critical temperature of T c % 280 K, which may be used in commercial solid-state thermoelectric (Peltier) coolers. 3 LCMO is also a ferromagnetic semiconductor with critical temperature T c % 230 K. 4,9 Several crystal structures have been identified, and it is confirmed that the ferromagnetic semiconductors LNMO and LCMO with high T c are P21/n monoclinic structure, in which octahedra with Ni (or Co) and Mn centers alternately stacking along (111).…”
mentioning
confidence: 99%
“…The t 2g bands for Mn and Ni do not appear in the DOS as the t 2g electrons for Mn 4+ and Ni 2+ have been considered to be classical core spins of S=3/2 and S=0 respectively. With the Mn core t 2g spin considered to be in up state at all sites, it is found that the minority (down) spin Ni e g band and the majority (up) spin Mn e g band lie in between the majority (up) spin Ni e g and the minority (down) spin Mn e g bands, as in the DFT DOS of Ref 6 . The Fermi energy lies in between the Ni e g and the Mn e g majority spin bands.…”
Section: Ordered Case: Dispersion and Dosmentioning
confidence: 72%
“…In La 2 NiMnO 6 the Nickel is in N i 2+ state (t ) and has three t 2g electrons 1,5,6 . As the t 2g electrons are more localized, and are parallel due to strong Hund coupling, they may be thought of as a core classical spin S = 3/2.…”
Section: The Model Hamiltonianmentioning
confidence: 99%